Estimation of near asteroids coordinates on CCD-frame - Соковикова, Наталья Сергеевна; Саваневич, Вадим Евгеньевич; Безкровный, Михаил Михайлович; Хламов, Сергей Васильевич (Eastern-European Journal of Enterprise Technologies, 2013)
The development of computational methods for highly precise estimation of near-Earth objects coordinates on a sampled image is of current importance nowadays due to a significant increase of penetrating power of optical systems. In this regard, it becomes much more difficult to achieve the required accuracy of observations of near-Earth objects with statistically dependent images. The paper proposes a method that allows potentially accurate estimation of coordinates of several near-Earth celestial objects on the CCD-frame. The developed method is based on the OLS assessment of parameters of statistically dependent objects images. The optimization problem of minimizing the sum of squared residuals (between theoretical and experimental brightness of the CCD matrix pixels) can be solved by the Levenberg-Marquardt algorithm. The developed method can be used in the systems of concurrent automatic detection of asteroids, for example, in the program CoLiTec, for estimating the coordinates of several near-Earth statistically dependent objects